Enhancing Capability of Human Resources Innovation - Sugianto, La Ode; Hartono, Sri (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2017)
This study aims to analyze the interrelationship of the variables of knowledge collection, knowl-edge contribution, organizational learning, and human resource innovation capability at Sultan Agung Semarang Islamic Hospital. This study also aims to develop a model of the role of com-munication variables in moderating the equation of enhancement of human resource innova-tion capability at Sultan Agung Semarang Islamic Hospital. The population in this study were all the permanent nurses at Sultan Agung Islamic Hospital who worked on the hemodialysis action room, surgery room, ICU, and SEC which totaled 75 people. Method of sampling in this research using census method. This research was analyzed using Sruktural Equation Mod-eling (SEM) with Partial Least Square (PLS) method using SmartPLS 2.0 M3 software. The results showed that knowledge gathering had a significant positive effect on the contribution of knowledge and to the capability of human resource innovation. Contribution of knowledge has a significant positive effect on organizational learning and on human resource innovation capability. Organizational learning has a significant positive effect on the capability of human resource innovation.